Observational insights into the compound environmental effect for 2-methyltetrols formation under humid ambient conditions. (February 2022) - Liang, Linlin; Engling, Guenter; Xu, Wanyun; Ma, Qianli; Lin, Weili; Liu, Xuyan; Liu, Chang; Zhang, Gen
Abstract: Laboratory experiments suggest acid-catalyzed aqueous-phase production can promote the formation of isoprene SOA, i.e., 2-methyltetrols. In this study we use ambient observations of the 2-methyltetrols along with other chemical measurements, as well as meteorological factors to investigate the relative importance of environmental influence for isoprene epoxydiols (IEPOX) SOA formation under atmospheric humidity conditions. The 2-Methyltetrols revealed good relationships with temperature and total solar radiation, but were weakly correlated with aerosol acidity and SO4 2− . EC-scaled 2-methyltetrols were observed to vary in a narrow pH range (1.5–2.0), indicating aerosol acidity was not a limiting factor for 2-methyltetrols formation. High values of 2-methyltetrols were consistently observed at high total solar radiation, the strong dependence of total solar radiation demonstrated that photochemical processes dominated 2-methyltetrols formation in humid environments. Although 2-methyltetrols can be enhanced by acid-catalyzed aqueous-phase reactions, it is not sufficient to compensate the synchronously weakened photochemical activity influence, leading to an obvious net decrease in the formation of 2-methyltetrols in the ambient. Moreover, aerosol droplet acidity was reduced under high liquid water content (LWC) condition, subsequently diminishing the enhancement of SOA formation by acidity. Overall, our results highlight that the environmental impact factors are highly variable and interplay, influencing the production of 2-methyltetrols, and suggest that the formation pathway of 2-methyltetrols is insensitive to aerosol acidity but dominated by photochemical production process in humid environments. Graphical abstract: Image 1 Highlights: EC scaled 2-methyltetrols show weak relationship with aerosol acidity and SO4 2− . 2-Methyltetrols formation is insensitive to acidity under humid ambient condition. 2-Methyltetrols formation is strong dependent on temperature in environment. Environmental factors are integrated influencing the production of 2-methyltetrols.